Catalysing entrepreneurship in and around universities. (19th September 2018) - Duruflé, Gilles; Hellmann, Thomas; Wilson, Karen
Abstract: In recent years universities have been taken by a new wave of entrepreneurial activities. Originally universities engaged with entrepreneurship mostly in terms of commercializing innovations based on research in the sciences. The new initiatives are instead focused on students and recent alumni, and encompass a much wider set of entrepreneurial initiatives, including student work spaces, accelerators programmes, or industry partnerships. This paper examines these emergent entrepreneurial activities in and around universities, and then asks what the role of government policy is. It argues that any policy approach will have to understand the multi-faceted nature of these new initiatives, and be sensitive to the porous nature of the boundaries between university and private-sector activities.